Kinetics of cytokine mRNA and protein expression by plastic adherent cells in the thymus after split-dose irradiation. (February 2019) - Nagayasu, Asako; Kakinuma, Shizuko; Nishimura, Mayumi; Shang, Yi; Sunaoshi, Masaaki; Tsuruoka, Chizuru; Ishihara, Hiroshi; Shimada, Yoshiya; Kobayashi, Yoshiro
Highlights: Irradiation caused dramatic changes in thymocyte number. Irradiation did not cause a dramatic change in plastic adherent cell number in the thymus. Irradiation increased IL-1β, IL-11, IL-12p40 and TNF-α mRNAs in plastic adherent cells. Expression of each of the four cytokine mRNAs was kinetically different. Abstract: Whole body irradiation causes significant apoptosis in various tissues such as the thymus. If apoptotic cells outnumber the phagocytic capacity of macrophages, apoptosis becomes secondary necrosis, inducing inflammatory cytokine expression in macrophages. Radiation also induces thymic lymphomas in C57BL/6 mice after four consecutive irradiations with 1.6 Gy X-rays with nearly 100% incidence. Since cancer development is modulated by a microenvironment involving macrophages, we examined the kinetics of thymocyte number and plastic adherent cell number in the thymus as well as cytokine mRNA expression by plastic adherent cells in the thymus after split-dose irradiation. Upon split-dose irradiation, thymocyte number changed dramatically, whereas plastic adherent cell number did not. Among cytokine mRNAs tested, IL-1β, IL-11 and IL-12p40 mRNAs were up regulated 2 days after the 1st and 2nd, 3rd and 4th, and 2nd and 3rd irradiations, respectively. On the other hand, TNF-α mRNA was up regulated 2 days after the 3rd irradiation and 2 weeks after the 4th irradiation. The level of IL-11 protein was also increased 2 days after 3rd and 4th irradiations. These results suggest that, upon split-dose irradiation, macrophages in the thymus produce various cytokines in a time-dependent manner, thereby contributing to induction of thymic lymphomas.